‘Run, Forrest, run!’ … or not? The Remarkable Migration of Forrest Gump from Winston Groom’s 1986 Novel to Robert Zemeckis’ 1994 Film. - Isabelle ROBLIN (E-REA)
“Run, Forrest, run!”: this famous quotation from Robert Zemeckis’ hugely successful Forrest Gump is in a way emblematic of the many transformations undergone by the original eponymous character in Winston Groom’s first person narrative in the process of adapting it for the cinema… since it does not even appear in the novel. Whenever novels are adapted and their characters migrate from the pages of the book onto the silver screen, their literary entity is necessarily altered to fit in with the requirements of the new medium. In the case of Forrest Gump however these alterations were quite extreme, for the nice, kind idiot of the film is radically different from the Forrest of the novel. The endings of the film and the novel also differ considerably, the sour sweet and conventional filmic closure fundamentally departing from the rather sad open ending of the picaresque novel. In this paper, I shall be concentrating on some of these obvious differences in the characterisation of Forrest without making value judgments on the perceived quality of the film or the novel, but by attempting to find out the reasons why the screenwriter and the director chose that very particular reading.